Etika Dakwah Ditinjau dari Perspektif Psikologi Komunikasi - Tomi Hendra; Sri Hartati (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
Da'wah is a very noble work and has been carried out by the Prophets and Apostles, especially the Prophet Muhammad. The part of Da'wah from a series of activities that invites, calls on, conveys the message of religion to others with the hope that there will be a shift from things that are not good to good, in the language of religion known as amar ma'ruf nahi mungkar. History has recorded a long journey from preaching from the Prophet Muhammad. Starting from da'wah carried out clandestinely to preaching carried out openly. History has also been proven in the journey of the preaching of the Prophet Muhammad, how his ethics in preaching. This paper seeks to put forward the da'wah ethics with the aim of the preachers or preachers having guidelines and guidelines in delivering the minutes and continuing the estates of the da'wah struggles carried out by the Prophet Muhammad. Many problems nowadays are found problems or problems that arise and occur in da'wah activities. One example is to think that someone else is wrong when they understand differently or conflict with the interpreter in delivering his message. In other cases, there are those who are explicitly speaking out words that can hurt others when preaching. The purpose of this paper is to try to raise and expose ethics in preaching, in the hope of contributing to the morning missionary practitioners